Governmental regulation and digital infrastructure innovation: The mediating role of modular architecture. (June 2023) - Henningsson, Stefan; Eaton, Benjamin D
In response to their growing importance, digital infrastructures (DIs) are increasingly subject to governmental regulation due to concerns over the downside risks posed by digital technologies to individuals and society. There is a general paucity of studies that address the impact of regulations on DI innovation. In addition, existing research presents seemingly contradictory findings on regulations governing digital technologies as both enabling and inhibiting innovation. This paper, therefore, elaborates on how different types of regulation impact various forms of DI innovation. We draw on modular systems theory to enrich extant conceptualisations of DIs and develop a related conceptual model that demonstrates the paths by which two types of DI regulation influence DI architectural modularity, which is proposed as a mediating mechanism that influences DI innovation. Our model makes a theoretical contribution through an in-depth explanation of the relationship between regulation and DI innovation by articulating and illustrating the effects of regulatory provisions and thereby extends the extant DI literature. In terms of practical implications, our model can help stakeholders both create DI regulation and respond to regulatory provisions.